Development of novel 9-O-substituted-13-octylberberine derivatives as potential anti-hepatocellular carcinoma agents. (31st December 2022) - Chen, Jichao; Duan, Yiping; Yu, Xiaoxuan; Zhong, Jiarou; Bai, Jing; Li, Nian-Guang; Zhu, Zheying; Xu, Jinyi
Abstract: A series of novel 9- O -substituted-13-octylberberine derivatives were designed, synthesised and evaluated for their anti-hepatocellular carcinoma (HCC) activities. Compound 6k showed the strongest activity against three human hepatoma cells including HepG2, Sk-Hep-1 and Huh-7 cells with IC50 values from 0.62 to 1.69 μM, which were much superior to berberine (IC50 >50 μM). More importantly, 6k exhibited lower cytotoxicity against normal hepatocytes L-02 with good lipid-water partition properties. The mechanism studies revealed that 6k caused G2/M phase arrest of the cell cycle, stabilised G-quadruplex DNA, and induced apoptosis via a mitochondrial apoptotic pathway. Finally, the in vivo anti-HCC activity of 6k was validated in the H22 liver cancer xenograft mouse model. Collectively, the current study would provide a new insight into the discovery of novel, safe and effective anti-HCC agents.